Business strategy formulation for â€œmix diner & floristâ€ to increase revenue, reduce cost, and attain sustainable competitive advantage - Faruq Nugroho, Aditya; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2016)
Abstract - Mix Diner & Florist is a company which conducts business in the food and beverage industry, specifically the industry of restaurant chain. Mix Diner & Florist was established in 2013, and has started to gain mainstream recognition since the beginning of 2015 due to larger mass media exposures, resulting in sharp increase in revenue and profits. Nonetheless, recently Mix Diner & Florist has been experiencing relative stagnation in its revenue, while at the same time; the overall cost has been steadily increasing overtime. The stagnation in revenue may be attributed to the recent increase in the level of rivalry among competitor in the industry. Consequently, the profit margin of Mix Diner & Florist has declined. In order to overcome the current problem, it is necessary for Mix Diner & Florist to formulate strategies to increase its revenue, reduce cost and attain sustainable competitive advantage. In order to achieve the aforementioned objectives, effective business strategies need to be formulated by conducting external and internal analysis on business environment through appropriate frameworks. The analysis in this paper is conducted through two main methods: qualitative methods, which includes interview with the management team of Mix Diner & Florist and, literature review of related journals and books, secondary data obtained from various sources, as well as primary data obtained directly from Mix Diner & Florist and first-hand research.Â  Based on the analysis, appropriate business strategies and recommended modified business model are formulated, which are focused mainly on increasing revenue, reducing cost, and attaining overall competitive advantage. Afterwards, the formulated business strategies are further derived to create implementation plan which caters to the above mentioned goals. The implementation plan includes, among others: price adjustments, creation of new menu offerings, partnership with service companies, operational improvement, and regular training for employees.Â Keywords: Business Strategy, Revenue Increase, Cost Reduction